"Whose Science? Whose Fiction?" Uncanny Echoes of Belonging in Samosata. (June 2015) - Stingl, Alexander I.; Weiss, Sabrina M.
This is the first of two special issues and the articles are grouped according to two themes: This first issue will feature articles that share a theme we call Technologies and the Political, while the second issue will feature the theme Subjectivities. However, we could equally consider them exercises in provincialization in the (counter)factual register in the first issue, and by affective historiography as conceptual-empirical labor(atory) in the second issue. What we have generally asked of all authors is to consider that the relation between science and society is often heavily influenced by and identified in the intermediary figurations portrayed in the genre of science fiction.